Empowerment of Social Capital Based on Religion to Espouse Employee Work Ethics at Al-Azhar Foundation Jakarta - Sarji Sarji; Ardianto Bayu Wibowo (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2021)
Trust is the essence of social capital. The Al-Azhar Islamic Boarding School Foundation (YPI) as an educational institution requires trust to survive and develop until now. As a religion-based foundation, the work ethic of employees is expected to be able to follow the religious norms that have been established so as to become a character for the institution. This research uses descriptive and exploratory approaches so that the researcher can clearly describe the concepts used in this research in detail. While the data was collected through observation and interviews from supervisors, administrators, supervisors, teachers, employees, alumni and the parents of YPI Al-Azhar. The results showed that employees and teachers at work prioritized service and honor than indicators of worship and trust. Employees at work are generally still transactional and pragmatic. So that the religious socio-religious capital, grace and sincerity that were imparted and inherited by the founders of Al-Azhar have not yet become the soul of the employees at work. Kepercayaan merupakan inti dari modal sosial. Yayasan Pesantren Islam (YPI) Al- Azhar sebagai lembaga pendidikan memerlukan kepercayaan untuk bertahan dan berkembang hingga saat ini. Sebagai yayasan yang berlandaskan agama, maka etos kerja karyawan diharapkan dapat mengikuti Norma agama yang sudah ditetapkan agar menjadi karakter bagi lembaga tersebut. Penelitian ini menggunakan pendekatan deskriptif dan eksploratif agar peneliti dapat menggambarkan dengan jelas konsep yang digunakan dalam penelitian ini secara rinci. Sedangkan data dikumpulkan melalui observasi dan wawancara dari pembina, pengurus, pengawas, guru, karyawan, alumni dan serta orangtua murid YPI Al-Azhar. Hasil penelitian menunjukkan bahwa para karyawan dan guru dalam bekerja lebih mendahulukan pelayanan dan kehormatan dibandingkan indikator ibadah dan amanah. Karyawan dalam bekerja pada umumnya masih bersifat transaksional dan pragmatis. Sehingga modal sosial religious, keikhlasan, ketulusan yang disemaikan dan diwariskan oleh para pendiri Al-azhar belum dapat menjadi jiwa dari para pegawai dalam bekerja.